Spatial Distribution of Weaknesses Areas and Maintenance Centers of Drinking Water Network in Ibb City Using Technique (GIS) (Journal of Libya for geographical studies, 2025)
This study seeks to use the descriptive approach to describing weaknesses areas the head of the pipes break sites of drinking water networks in Ibb during the period between (2020-2023), as well as the use of analytical curriculum and conduct a spatial analysis process for classes used to build the best and most suitable sites for building the maintenance of drinking water networks, one of the most important results of this study amounted to cases broken network pipes processed during the period (2020-2023), 3384, including 1057 break case, 31.2%, the AL-Meshnah directorate came first in the number in cases of broken pipes, it reached 1691 break case, which is 50%, while the AL-Dahar directorate came second 1602 break case, 47.3%, finally the study suggests 5 sites, as the best sites to build maintenance centers for drinking water networks in Ibb city, suggested sites are AL-Moaqbah mountain maintenance center, Fiat maintenance center, street 16 will maintenance center, Kahab maintenance center, and finally AL-Salabah maintenance center.
Keywords: Break the Pipes; Waterproofing; Rehabilitation and Maintenance of the network; Information Standards; Maintenance Centers